NUMERICAL MODELLING OF HOMOGENEOUS TWO-PHASE GAS-LIQUID FLOW IN A PIPE (Jurnal Teknologi (Sciences & Engineering), 2015)
A one-dimensional model which represent a system of partial differential equations that describe mathematically the two-phase flow has been considered for the gas-liquid mixture flow in a pipeline. The Implicit Steger -Warming flux vector splitting method is used for the numerical computation on air-water compressible flow problems. The results for pressure wave propagation, celerity or speed of sound and mass flow rate for different values of mass ratio were obtained. It was observed that the propagation of pressure along the pipeline and the mass flow rate there decreases along the pipe and maintained near a steady flow until it reaches the downstream of the pipe signifying the effect of gas build up during the pump control in pipeline.